О цикле развития трихомонад - Падченко, И.К. (Вестник зоологии, 1975)
Using of the original procedure of continuous cultivation in the research permitted specifying that polymorphism was observed in Trichomonadidae family only in the process of their reproduction. Absence of cyst stage in these Protozoa is proved. It is established that multiple reproduction in Trichomonadidae arises as a result of the effect of sublethal doses of different chemical substances.